Inteligencia Artificial aplicada al aprendizaje de ciencias naturales para el 5to año de educación básica de la Unidad Educativa Santa Mariana de Jesús, periodo lectivo 2024- 2025. - Loor Reinoso, María Viviana (2025)
The purpose of this research is to analyze and apply the use of artificial intelligence (AI) tools in the teaching-learning process of the Natural Sciences area, with a specific focus on fifth-year elementary school students at the Santa Mariana de Jesús Educational Unit, during the 2024– 2025 academic year. An initial assessment revealed significant difficulties in understanding scientific concepts, lack of motivation for the subject, and limited active student participation, all attributable to the use of traditional methodologies focused on exposition and memorization. Faced with this problem, a technological proposal was designed based on the pedagogical use of three accessible tools based on artificial intelligence: Canva (for the creation of interactive visual resources), Leonardo AI (for the generation of contextualized scientific images), and ChatGPT (as a virtual assistant for explaining and resolving questions). The proposal was developed using a qualitative and descriptive methodological approach, with a pedagogical intervention design. Techniques such as direct observation, teacher surveys, and diagnostic and final evaluations were applied to students before and after the implementation of the teaching strategy. During the implementation phase, teachers participated in a structured training program that allowed them to acquire skills to integrate technological tools into their classrooms. Subsequently, educational resources designed with AI were applied in the classroom, and their impact was evaluated using monitoring and formative assessment instruments. The results obtained showed a significant improvement in academic performance, greater content comprehension, increased motivation, and active student participation in both individual and group tasks. In conclusion, it is demonstrated that the incorporation of artificial intelligence in education, when guided by pedagogical and ethical criteria and adapted to the students' cognitive level, represents an innovative and effective alternative for improving teaching and learning processes, especially in the area of Natural Sciences in basic education.